Cognitive Dysfunctions in Inflammatory Bowel Disease and Irritable Bowel Syndrome - Bagnasco, Mariana Suárez (Journal of Medicine, 2020)
The aim of this paper is to summarize the current evidence on cognitive dysfunctions in adults with inflammatory bowel disease and inflammatory bowel syndrome.The online databases PubMed and PsycINFO were searched. All quantitative studies published in English found in the mentioned databases until December 2019 were included. Quantitative studies which did not include a control group, qualitative studies and case studies were excluded. We found seven papers about cognitive dysfunctions in IBD and IBS. Four of seven papers compare cognitive functions of patients with IBD and IBS. Three of seven studies assess cognitive functions in IBD. Three papers assessed memory, three papers studied selective attention and inhibition response, two papers assessed cognitive flexibility, one paper measured information processing speed, and one paper assessed verbal fluency. J MEDICINE JUL 2020; 21 (2) : 102-104